Resiliensi Atlet Kabupaten Banyuasin Menuju Porprov Xiv Sumsel 2023 Di Lahat - Hengki Kumbara; Husni Fahritsani; Daryono Daryono; Bayu Iswana (Universitas Negeri Padang, 2022)
The purpose of this study was to find out how much resilience Banyuasin district athletes had in dealing with South Sumatra Province XIV in Lahat District. The method used is a survey method. The data collection technique used an athlete resilience questionnaire with a reliability of 0.742 questions as many as 19 questions. Data analysis used percentage description. The results of the study stated that the average athlete who had optimism in facing porprov XIV was 85.53% with good criteria. The average ability of athletes to adapt to the situation is 83% with good criteria. The average ability of athletes in dealing with problems during training is 83.25% with good criteria. The average ability of athletes to solve problems during training is 82.67% with good criteria.